Espiritualidades queer: heterotopías de la igualdad en la diferencia = Queer spiritualities : heterotopias of equality in difference - Bárcenas Barajas, Karina (Ciencias sociales y religión, 2016)
The tendency to religious deinstitutionalization has revealed a variety of practices and beliefs assemblies that realize the centrality of spirituality to understand the dynamics of the religious field. Queer spiritualities are also part of this trend that through access to the goods of salvation for here and now people with orientations and non-heterosexuals identities, such as LGBT, build a relationship with God thatsubjectively enables them to reconcile their sexual orientation and gender identity, their way of inhabiting the world, with an amalgam of beliefs and practices originated in different religions and spiritualities present in different traditions. The paradigmaticcase of Mandala Group realizes the dynamics of queer spirituality in religious field through subjectification and individualization of beliefs, but especially of a heterotopiadefined by equality in difference.